ANALISIS PROSPEK USAHA KEMASAN TELUR (EGG TRAY) DI KOTA TIMIKA - Otniel Imanuel Gobai; Rulan L. Manduapessy (Jurnal Ekonomi dan Bisnis, 2026)
This study aims to analyze the business prospects of the egg packaging industry in Timika City. The research method used is descriptive. Data collection techniques included in-depth interviews with egg farmers, used cardboard collectors, and officials from the Mimika Regency Livestock and Industry Office. The data analysis instrument used was the Milles and Hubberman model. The results of the study indicate that there is significant business potential due to the abundant availability of cardboard raw materials and the high demand for packaging from local farmers. The wide-open market opportunities serve as the primary supporting factor for the growth of this business. Based on these findings, it can be concluded that the egg packaging business in Mimika Regency has promising prospects and the potential to generate economic benefits for business operators.